Entre experiencia e invenção: Incidencias autobiográficas em Antonio Torres - Gonçalves, Rogério Gustavo [UNESP] (FapUNIFESP (SciELO), 2016)
In Antonio Torres' literature, the presence of artistically elaborated elements that refer to personal experiences and specific features of his life causes the memorialism that governs the telling of the characters' story to interfuse, at times, with the writer's own intimate memories. Based on these aspects, this paper aims to explore the procedures of fictionalization of experiential data in Antonio Torres' novels, given its relevance to the development of the narrative and to the author-text-reader relation. From the dialogic reading of the author's body of work, we seek to define a writer's myth or a literary personality and the consequent edification of an autobiographical space that translates to a singular fictional universe where characters, issues and situations are often recurring, producing a communicative connection between the texts and causing the immediate familiarization of the reader. Besides the production of a literary image of Antonio Torres, we examine how the migration of personal elements to his work allows the social-political reality he witnesses to penetrate into the fictional plan. Resorting to his homeland and his people to portrait the impact of social transformations on the backwoods population, the author's work ends up reflecting the need to show the identity crisis of the backwoods northeastern, clinging to memories of a past that is no longer connected to the present.
Between experience and invention: Autobiographical incidences in AntonioTorres' fiction
Keywords: Antonio Torres; Autobiographical space; Fictional memorialism; Self-referential literature